Uptake of HIV/AIDS Services Following a Positive Self-Test Is Lower in Men Than Women in the Democratic Republic of the Congo - Tonen-Wolyec, Serge; Kayembe Tshilumba, Charles; Batina-Agasa, Salomon; Tagoto Tepungipame, Alliance; Bélec, Laurent (Frontiers in Medicine, 2021)
As far as HIV self-testing (HIVST) is concerned, proving the link to HIV care for users with a positive result contributes to understanding the implementation of HIVST. We sought to examine whether there were differences by sex in the uptake of HIV services following a positive self-test in the Democratic Republic of the Congo (DRC). This was a mixed-methods study exploring linkage to care for HIVST through a secondary analysis of collected data from three pilot surveys recently conducted in three cities (Kinshasa, Kisangani, and Kindu) during 2018 and 2020 in the DRC. Linkage to HIV care was defined as delayed when observed beyond one week. A total of 1,652 individuals were self-tested for HIV. Overall, the proportion of linkage to HIV care was high (n=258; 82.2%) among individuals having a positive result with HIV self-test (n=314), but it was significantly lower in men (65.2%) than women (89.2%). Furthermore, linkage to HIV care of men was significantly delayed compared to women (40.0% versus 20.7%). These findings show a lower uptake of care following a positive self-test in men than women. This trend already previously observed in sub-Saharan Africa shed light on the need to increase linkages to care among men newly diagnosed through HIV self-testing.